2021
DOI: 10.3389/fmech.2021.630324
|View full text |Cite
|
Sign up to set email alerts
|

Critical Ignition Conditions of Wood by Cylindrical Firebrands

Abstract: This study investigated the thermal conditions preceding ignition of three dense woody fuels often found on structures by firebrands, a major cause of home ignition during wildland-urban interface (WUI) fires. Piles of smoldering cylindrical firebrands, fabricated from wooden dowels, were deposited either on a flat inert surface instrumented with temperature and heat flux sensors or on a target fuel (marine-grade plywood, oriented-strand board, or cedar shingles) to investigate critical conditions at ignition.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 32 publications
4
24
0
1
Order By: Relevance
“…Hakes et al [29] and Salehizadeh [31] measured temperatures in a pile of embers using type K thermocouples and thin skin calorimeters. They recorded higher temperatures with larger piles and at the center of the pile.…”
Section: Temperature Measurements Of Embersmentioning
confidence: 99%
See 4 more Smart Citations
“…Hakes et al [29] and Salehizadeh [31] measured temperatures in a pile of embers using type K thermocouples and thin skin calorimeters. They recorded higher temperatures with larger piles and at the center of the pile.…”
Section: Temperature Measurements Of Embersmentioning
confidence: 99%
“…However, it is the heat transfer from the ember to the combustible substrate it lands on that determines the ignition propensity of the substrate. Following the pioneering work by Manzello et al [21] and researchers [29,31,32] at the University of Maryland, recent studies [34,87] have reported on high resolution heat flux measurements from smoldering embers.…”
Section: Thermal Energy Measurementsmentioning
confidence: 99%
See 3 more Smart Citations